2019
DOI: 10.3390/ijms21010156
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory-Related Quality of Life in Multiple Chemical Sensitivity: A Genetic-Acquired Factors Model

Abstract: Genetic polymorphisms as well as environmental exposures to chemical compounds, iatrogenic, psychological, and physical trauma may play a pathophysiological role in multiple chemical sensitivity (MCS) olfactory complaints, given that xenobiotic metabolism is influenced by sequence variations in genes of metabolizing enzymes. Thus, the aim of the present study was to depict—by means of multiple regression analysis—how different genetic conditions, grouped according to their function as well as clinical backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 117 publications
0
15
0
Order By: Relevance
“…Interestingly, given that A2AR is abundantly present in olfactory bulb [34], it is possible to hypothesize that a defective activation of A2AR signaling pathway, caused by genetic defects, may play a role in smell alterations that are reported by MCS patients. Indeed, it has recently been shown that olfactory complaints in MCS patients rely on a complex interaction between genetic and acquired factors, mainly represented by toxic environmental stimuli [35].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, given that A2AR is abundantly present in olfactory bulb [34], it is possible to hypothesize that a defective activation of A2AR signaling pathway, caused by genetic defects, may play a role in smell alterations that are reported by MCS patients. Indeed, it has recently been shown that olfactory complaints in MCS patients rely on a complex interaction between genetic and acquired factors, mainly represented by toxic environmental stimuli [35].…”
Section: Discussionmentioning
confidence: 99%
“…Central sensitization induces many functional, molecular and structural modifications. As a consequence, the prospect of establishing a unique definition including all these disorders is remote [ 1 , 2 ]. Several neurobiological aspects have been postulated as the likely routes of pathological models, such as classical conditioning, biochemical disruptions and neurogenic inflammation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the prospect of establishing a unique definition including all these disorders is remote [ 1 , 2 ]. Several neurobiological aspects have been postulated as the likely routes of pathological models, such as classical conditioning, biochemical disruptions and neurogenic inflammation [ 2 ]. These may play a role in a wide spectrum of physiopathological central nervous system responses associated with specific regions of the brain that are connected with emotional and motivational processing of information, like the limbic area (amygdala, hippocampus) and the olfactory and the auditory efferent systems [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations